Developments and Potential Management Issues of a Perennial Hot Selling Cut Flower Case - Чі-Фонг Фен; Лі-Чун Хуан; Ю-Чан Чіу (Plant Varieties Studying and Protection)
Purpose. The commercial life of cut flower varieties was generally considered to be as short as fashion. However, this study provides an example of a perennially popular cut flower variety that offers an alternative perspective on the potential of the cut flower market.